Case report: A case of injury to the infrapatellar branch of the saphenous nerve caused by medial approach in knee arthroscopy - Tan, Jiyang; Wang, Xunhao; Xiong, Fei; Qian, Jun; Ying, Qiuwen; Mi, Jingyi (Frontiers in Neurology, 2023)
The patient presented was a 72-year-old male and was referred to our department for treating the pain in the anteromedial infrapatellar side of the right knee with a sensory disturbance that began two years earlier. The patient previously underwent right knee arthroscopy at another hospital for a meniscus injury two years ago, which gave her relief from the knee pain, while the pain and discomfort near the incision of the medial portal persisted. Given this situation, some physical treatments, such as ice compress, were taken postoperatively. However, the symptom was only partially relieved before discharge. Subsequently, the patient visited two other hospitals and began taking oral pregabalin and duloxetine for treatment according to the diagnosis of right common peroneal nerve injury. The pain in the same dermatomal distribution was slightly relieved, but a withdrawal reaction was observed. Differently, the ultrasound result in our hospital reported that the right medial quadriceps femoris tendon showed a hypoechoic area considering inflammatory changes. Physical examination of the right knee detected atrophy of quadriceps femoris muscle, decreased muscle strength (M4), obvious tenderness in the medial side, radiating pain along to the anterior tibia, sensory disturbance (S3+), and the negative results in drawer test, McMurray test, pivot shift test, as well as a lateral stress test. Based on the above evidence, the diagnosis was drawn as the injury of the infrapatellar branch of the saphenous nerve, after which neurolysis of the particular nerve was operated. An enlarged incision was made along the original medial approach. Scar hyperplasia was observed after careful separation of the subcutaneous tissue. During the neurolysis, branches were found wrapped in the scar, while their continuity and integrity were confirmed after relief. The released nerve was placed in a physiological position. The pain was relieved obviously, and the numbness disappeared on the first postoperative day. At the one-month follow-up, all the symptoms were cured.